Antioxidant and antibacterial activity of red seaweed Kappaphycus alvarezii against pathogenic bacteria - P. Bhuyar; M.H. Rahim; S. Sundararaju; G.P. Maniam; N. Govindan (Global Journal of Environmental Science and Management, 2020)
Seaweeds can produce variety of bioactive components for the benefits of humans. Malaysia is one of the countries to produce red seaweeds, which are popular secondary metabolites. Kappaphycus species, largest tropical red algae exhibit the high growth rate. It was reported that its biomass can grow double in just 15 to 30 days. Therefore, this investigation emphasized on two extraction methods such as hot water and ethanolic Soxhlet extraction to extract the bioactive compounds from Kappaphycus alvarezii. Both of theseextractions were screened to produce antimicrobial and antioxidants compounds. Total phenolic content and ferric reducing assays were employed to quantify antioxidant properties. Whereas, the disc diffusion assays were used to study antibacterial activity. The results reported the highest phenolic content for ethanolic extract (20.25 ± 0.03 mg gallic acid equivalents per gram of extract). On the other hand, the value of phenolic content was slightly decreased 19.1 ± 0.81 mg gallic acid equivalents per gram of extract for the hot water extract. It was also found that both the extracts were potentially capable of balancing reactive oxygen species. Disc diffusion assay results indicated that the extract of red alga K. alvarezi were more efficient against B. cereus. Among the fatty acids determined levoglucosenone and 4-Pyridinemethanol were present in high percentages in hot water extract whereas Hexamethyl- cyclotrisiloxane followed by 1, 2, 5- Thiadiazole-3-carboxamide, 4-[(2-chloroethyl) amino]-N-(2-hydroxyethyl) were present in ethanolic extract of K. alvarezi. The present study concluded that, hot water extracts of K. alvarezii can be used for large scale production of bioactive compounds utilizing an easily available potential seaweed. Future research of red seaweed will be highly important for pharmaceutical and medicinal field as well as a homogenizer in milk products, toothpaste and jellies in other industrial applications.